SERVICES IMPLEMENTED AT SELECTED DRUG REHABILITATION CENTERS IN CAVITE: AN ASSESSMENT - Ruby Ann L., Espineli; Marissa C., Lontoc; Myleen P., Legaspi (European Scientific Journal, ESJ, 2015)
The study mainly assessed the services implemented on drug rehabilitation centers in Cavite. Three out of six drug rehabilitation centers in Cavite gave their consent to conduct the study in their centers. Survey questionnaire and interview of the administrators, program facilitators and patients were utilized to gather necessary data.The findings showed that in terms of operational management, all centers strictly follow the standards set by Department of Health (DOH). On the other hand, most of the program facilitators are on-call.In terms of administrator and program facilitators, they are always on time in performing their duties but the center could not maintain its employees due to lack of provision on security of tenure.In terms of resources, all is properly monitored. They have division of budget for their operation. On the other hand, two of the centers lack financial support from NGO for their trainings. Findings further revealed that, centers established linkages with religious groups. Every phase of their activities often involve religious adoration. In contrast, there is limited linkage with local and non-government agencies in support to the traditional healing of the patient.In terms of physical facility, its privacy and comfort helps in the immediate recovery of the patient.Further, evaluation conducted by program facilitators is indispensable in the formulation of individualized treatment program.Moreover, monitoring of patients is also done through interaction with them. They also keep in touch with their graduated patients.